Pengaruh Pemberian Terapi Akupresur dan Infused Water Lemon Terhadap Penurunan Mual Muntah Pada Ibu Hamil Trimester 1 di Klinik Wicaksana Laghawa Sangatta Utara - Ratih Anita; Siti Noorbaya; Rr. Nindya Mayangsari (Akademi Kebidanan Bunga Husada Samarinda, 2025)
Introduction: Excessive nausea and vomiting (emesis gravidarum) remain a significant issue during pregnancy, affecting approximately 0.3-3% of pregnant women. Acupressure therapy at the Pericardium 6 point and lemon-infused water have been proven effective in reducing nausea and vomiting in first-trimester pregnant women, with no side effects as they do not involve the use of chemicals. Objective: This study aims to analyze the effect of acupressure therapy and lemon-infused water on reducing nausea and vomiting in pregnant women at Wicaksana Laghawa Clinic, North Sangatta. Methods: This experimental study utilized a two-group pretest-posttest design. The sample consisted of 24 pregnant women selected using purposive sampling. Data were collected using the PUQE-24 questionnaire and analyzed with a paired samples test. Results: Before therapy, the average nausea and vomiting score in the acupressure group was 11.57, which decreased to 3.79 after therapy. In the lemon-infused water group, the initial average score of 9.86 decreased to 3.64. The analysis showed that both therapies were significantly effective (p-value = 0.000; p < 0.05) in reducing nausea and vomiting in pregnant women. Conclusion: Both acupressure and lemon-infused water therapies are effective in reducing the severity of nausea and vomiting. Further research is recommended to explore the interaction between the two therapies and consider environmental and psychosocial factors influencing the outcomes.